Suicidal digoxin intoxication in 61 year old patient - Ciechański, Erwin; Ciechański, Krystian Lech; Tchórz, Michał (Journal of Education, Health and Sport, 2019)
Digoxin is one of the oldest drugs used in cardiology. It belongs to subgroup of cardiac glycosides. Currently, due to limited indications for use, cases of poisoning with this group of drugs are becoming less common. Ease of poisoning results from the low therapeutic index and symptoms of intoxication may include many different systems. The most serious symptoms of overdose are cardiac arrhythmias. We present a case of a patient with suicide poisoning due to ingestion of 30 tablets of 0.1mg digoxin.